2012
DOI: 10.5539/jas.v4n12p93
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture and Plant Canopy Temperature Sensing for Irrigation Application in Cotton

Abstract: There is a need to provide technical tools to cotton producers for appropriate management of irrigation in the Mid-South region of the U.S.A wireless sensor network was deployed in a cotton field to monitor soil water status for irrigation. The network included two systems, a Decagon system and a microcontroller-based system. The Decagon system consisted of soil volumetric water-content sensors, wireless data loggers, and a central data station. Sensor data collected by each data logger were wirelessly transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Much research has been done on the use of sensors and the global positioning system (GPS) to gather information on soil and plant conditions, which includes using electrical conductivity sensors to map soil electrical conductivity (EC) (Rhoades et al, 1997;Kitchen et al, 1999;Fraisse et al, 2001;Johnson et al, 2003), soil moisture sensors to measure soil moisture content or soil water potential (Dukes and Scholberg, 2004;Evett and Parkin, 2005;Robinson et al, 2008;Vellidis et al, 2008;Sui and Baggard, 2015), thermal irradiation sensors to detect plant canopy temperature (Jackson, 1986;Cohen et al, 2005;O'Shaughnessy and Evett, 2009;Sui et al, 2012), spectral reflectance and ultrasonic sensors to predict plant health characteristics (Sui et al, 1989;Kostrzewski et al, 2003;Sui and Thomasson, 2006;Detar et al, 2006;Yin et al, 2012, Sui et al, 2013, and mass-flow sensors to map crop yields (Searcy et al, 1989;Grisso et al, 2009;Thomasson and Sui, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been done on the use of sensors and the global positioning system (GPS) to gather information on soil and plant conditions, which includes using electrical conductivity sensors to map soil electrical conductivity (EC) (Rhoades et al, 1997;Kitchen et al, 1999;Fraisse et al, 2001;Johnson et al, 2003), soil moisture sensors to measure soil moisture content or soil water potential (Dukes and Scholberg, 2004;Evett and Parkin, 2005;Robinson et al, 2008;Vellidis et al, 2008;Sui and Baggard, 2015), thermal irradiation sensors to detect plant canopy temperature (Jackson, 1986;Cohen et al, 2005;O'Shaughnessy and Evett, 2009;Sui et al, 2012), spectral reflectance and ultrasonic sensors to predict plant health characteristics (Sui et al, 1989;Kostrzewski et al, 2003;Sui and Thomasson, 2006;Detar et al, 2006;Yin et al, 2012, Sui et al, 2013, and mass-flow sensors to map crop yields (Searcy et al, 1989;Grisso et al, 2009;Thomasson and Sui, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that soil water sensors can effectively be used for irrigation scheduling. However, procedures for proper installation, calibration, and maintenance of soil water sensing devices are critical for the success of the sensor-based irrigation scheduling (Yoder et al, 1997;Leib et al, 2003;Evett et al, 2006;Sui et al, 2012).…”
Section: Soil Sensorsmentioning
confidence: 99%
“…According to Nedic & Eric (2014), metal cutting temperature was measured with artificial thermocouple and metal machine-ability was analyzed from aspect of cutting temperature. In Sui et al (2012), LM35 and PIC16F873 microcontroller was used to build a device which can measure safely the indoor temperature in firm buildings such as greenhouses, warehouses or silos. Afsarimanesh and Ahmed (2011) used AT89C51 and LM35 to build a system which measures temperature and stores them in the EEPROM of the microcontroller.…”
Section: Related Design Literaturementioning
confidence: 99%